Utilizing Customer List Menu To Monitoring Customer Data On Web Based Accounting Online System 2.0 - Martono, Aris; Mulyati​, Mulyati​; Maesaroh, Siti (Pandawan, 2017)
In a customer company is one component in advancing the company. Serving and protecting customers is something every company should do. Customer is a king who can change the situation on the company. But the customer must also be monitored so as not to be arbitrary to the company. Company monitoring must be done by a company for the convenience of the company. Customers who violate the rules and can not comply with the conditions set by the company may harm the company in the future. In order for the company to lose nothing it will have to do things like create new customers, add customer lists, change and delete customer lists, customer memo credits and record the balance of customer receivables is a company's monitoring activities to its customers. The use of WBAOS 2.0 (Web Based Accounting Online System) can facilitate the company in performing customer monitoring as well, in addition to accounting activities. By using the system the company can monitor customers anytime and anywhere with the internet connected. So that monitoring can run more effectively and more efficiently.